2010
DOI: 10.1007/s11764-010-0157-3
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of unpartnered men with prostate cancer: a qualitative analysis

Abstract: Purpose The purpose of this study was to examine how men without partners make decisions about prostate cancer treatment, manage treatment side effects, and obtain information and support. Background In 2009, it was projected that over 230,000 men were diagnosed with prostate cancer. While treatment options vary, these options result in changes within the man that can affect his quality of life. Research has shown that often spouses play a central role in men’s choice of treatment and in maintaining men’s qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 29 publications
2
45
0
1
Order By: Relevance
“…The importance of these two roles played by the spouses was consistent with the overall findings of Kazer et al . () who reported one of the main challenges un‐partnered men with prostate cancer had was of ‘going it alone’. Spousal support is also another example of how theoretical approaches such as the Theory of Planned Behaviour's concept of subjective norms can help explain determinants of health behaviours like physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of these two roles played by the spouses was consistent with the overall findings of Kazer et al . () who reported one of the main challenges un‐partnered men with prostate cancer had was of ‘going it alone’. Spousal support is also another example of how theoretical approaches such as the Theory of Planned Behaviour's concept of subjective norms can help explain determinants of health behaviours like physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…The multivariable model included covariates identified in previous literature as associated with HIV status and sexual and urinary outcomes after prostate cancer: age, race, type of prostate cancer treatment, relationship status, and preferred role in sex . Because the physical and mental comorbidities assessed in our study may lie on the causal pathway between HIV status and HRQOL, they were not included in models.…”
Section: Methodsmentioning
confidence: 99%
“…This life situation had a signifi cant negative impact on QoL after radiotherapy. Previous research showed that married men with prostate cancer turned to spouses for support and assistance [21], and that some prostate cancer patients with no partner have specifi c coping needs that have to be obviated [22]. Therefore, men living alone may need special attention.…”
Section: Living Alonementioning
confidence: 99%